Sleep Terrors in Twins - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
In an attempt to clarify the genetic and environmental causes of sleep terrors in childhood, reasearchers in Canada followed 390 pairs of monozygotic and dizygotic twins by assessing the frequency of sleep terrors at 18 and 30 months of age using a questionnaire administered to the biological mothers.